Fourth meeting of the Eastern Mediterranean Acute Respiratory Infection Surveillance (EMARIS) network and first scientific conference on acute respiratory infections in the Eastern Mediterranean Region, 11-14 December, 2017, Amman, Jordan - Abdinasir Abubakar; Amal Barakat; Amira Ahmed; Amjad El Kholy; Lora Alsawalh; Lubna Al Ariqi; Mamunur Rahman Malik; Majdouline Obtel; Mohammad Sahak; Pamela Mrad; Soumia Triki; Salah Al Awaidy; et al. (Elsevier, 2020)
Influenza causes significant morbidity and mortality worldwide. Owing to its ability to rapidly evolve and spread, the influenza virus is of global public health importance. Information on the burden, seasonality and risk factors of influenza in countries of the World Health Organization Eastern Mediterranean Region is emerging because of collaborative efforts between countries, WHO and its partners over the past 10 years. The fourth meeting of the Eastern Mediterranean Acute Respiratory Infection Surveillance network was held in Amman, Jordan on 11-14 December 2017. The meeting reviewed the progress and achievements reported by the countries in the areas of surveillance of and response to seasonal, zoonotic and pandemic influenza. The first scientific conference on acute respiratory infection in the Eastern Mediterranean Region was held at the same time and 38 abstracts from young researchers across the Region were presented on epidemiological and virological surveillance, outbreak detection and response, influenza at the animal-human interface, use and efficacy of new vaccines to control respiratory diseases and pandemic influenza threats. The meeting identified a number of challenges and ways to improve the quality of the surveillance system for influenza, sustain the system so as to address pandemic threats and use the data generated from the surveillance system to inform decision-making, policies and practices to reduce the burden of influenza-associated illnesses in the Region. Keywords: EMARIS, Influenza, Eastern Mediterranean Region, WHO